Comparative cytotoxicity of ionic and non-ionic radiocontrast agents on MDCK cell monolayers in vitro. - Schick, Cornelia Sonja; Haller, Christlieb (Nephrology, dialysis, transplantation, 1999)
BACKGROUND: Intravascular radiocontrast agents may cause acute renal failure, particularly in patients with pre-existing renal insufficiency. Direct cytotoxic effects of radiocontrast agents on renal tubular cells may contribute to the pathogenesis of radiocontrast-induced nephropathy. METHODS: We analysed the cytotoxicity of the ionic radiocontrast agents diatrizoate (monomeric) and ioxaglate (dimeric), as well as of the non-ionic radiocontrast agents iohexol (monomeric) and iodixanol (dimeric) on the renal epithelial Madin Darby Canine Kidney (MDCK) cell line grown on permeable supports. The toxicity assays assessed cell viability, transmonolayer resistance and inulin permeability between the apical and basal cell culture compartment. In addition, the distribution of the tight-junction-associated membrane proteins ZO-1 and occludin was analysed using immunofluorescence microscopy. RESULTS: In all assays the high osmolal ionic compound diatrizoate had significant cytotoxic effects that included the partial redistribution of the tight-junction-associated membrane proteins into a cytoplasmic compartment. To a lesser extent this redistribution also occurred with the dimeric ionic compound ioxaglate, but not with the non-ionic radiocontrast agents. With regards to cell viability, transmonolayer resistance and inulin permeability the radiocontrast agents with reduced osmolality were significantly less toxic than diatrizoate, independent of their ionic strength. CONCLUSIONS: Physicochemical factors contribute to the cytotoxicity of radiocontrast agents in vitro. The redistribution of tight-junction-associated membrane proteins by the ionic radiocontrast agents corresponds with the loss of the barrier function of the epithelial cell monolayer, which is a major pathophysiological mechanism in acute renal failure. The radiocontrast agents with reduced osmolality are less cytotoxic than diatrizoate, independent of their ionicity. Hyperosmolality appears to be a more important determinant of the cytotoxicity of diatrizoate than ionic strength.